Identifying foods with good nutritional quality and price for the Opticourses intervention research project. Issue 17 (14th September 2017) - Dubois, Christophe; Tharrey, Marion; Darmon, Nicole
Abstract: Objective: People on a limited budget want to know the 'good price' of foods. Here we report the methodology used to produce an educational tool designed to help recognize foods with good nutritional quality and price, and assess the validity and relevancy of the tool. Design: A 'Good Price Booklet' presenting a list of foods with good nutritional quality and price was constructed. The validity of the in-booklet prices was assessed by comparing them with prices actually paid by households from the Opticourses project. The relevancy of the booklet tool was assessed by semi-structured interviews with Opticourses participants. Setting: Socio-economically disadvantaged neighbourhoods of Marseille, France. Subjects: Ninety-one participants collected household food-purchase receipts over a 1-month period. Results: Based on the French food database, foods with higher-than-median nutritional quality were identified. After grouping similar foods, 100 foods were selected and their corresponding in-booklet prices were derived based on the distribution of average national prices by food group. Household food purchases data revealed that of the 2386 purchases of foods listed in the booklet, 67·1 % were bought at prices lower than the in-booklet prices. Nineteen semi-structured interviews showed that participants understood the tool and most continued using it more than a month after the intervention. Conclusions: A method was developed to ease the identification of foods with good nutritional quality and price. The Good Price Booklet is an effective tool to help guide people shopping on a low budget.